2021
DOI: 10.26858/sosialisasi.v0i3.19958
|View full text |Cite
|
Sign up to set email alerts
|

Remaja Putus Sekolah Pada Komunitas Pekerja Sawah Di Desa Leworeng Kecamatan Donri-Donri Kabupaten Soppeng

Abstract: Penelitian ini bertujuan untuk mengetahui bagaimana faktor penyebab remaja putus sekolah dan peran orang tua dalam menghadapi remaja yang putus sekolah di Desa Leworeng Kecamatan Donri-Donri kabupaten Soppeng. Penelitian ini bersifat deskriptif kualitatif yang menggambarkan masalah remaja putus sekolah Hasil penelitian menunjukkan bahwa orang tua di Desa Leworeng tidak mampu  menjalankan menjalankan fungsi keluarga dengan baik sehingga anaknya putus sekolah, hal ini dikarenakan  tingkat pendidikan orang tua ya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
(2 reference statements)
0
1
0
1
Order By: Relevance
“…Children no longer in school are considered to be able to find their livelihood. The existing culture is that parents will let their children go after they are not in school (Ramli, 2021).…”
Section: Child Labormentioning
confidence: 99%
“…Children no longer in school are considered to be able to find their livelihood. The existing culture is that parents will let their children go after they are not in school (Ramli, 2021).…”
Section: Child Labormentioning
confidence: 99%
“…Previous research indicated that adolescent farmers in the Donri-Donri subdistrict dropped out of school due to their preference for earning money from the harvest and working on farms, often transporting rice on motorbikes. Furthermore, parents' support for remaining in school is decreasing, as education is viewed as expensive and allowing children to work and earn their own money is seen as a viable alternative (Mauliadi Ramli, 2022). In previous research on adolescents' knowledge about early marriage, it was found that education significantly impacts their decision to marry early and their ability to make decisions as a married couple.…”
Section: Introductionmentioning
confidence: 99%
“…muta 'al & Sa'adah, 2022;Ramli, 2021), menggantikan tempat pendidikan keluarga, sehingga orang tua melepaskan tanggung jawab bila anaknya sudah bersekolah (Heryanto, 2017;Sidharta, 2021). Tanggung jawab pendidikan seolah-olah beralih dari orang tua ke tangan guru (Amanda, 2022;Baslini, 2022).…”
unclassified